Experimental and numerical investigations of pitch-plunging wing aerodynamics at low Reynolds number. (1st January 2013) - Wokoeck, Ralf; Radespiel, Rolf; Ehlers, Hauke; Konrath, Robert
In the present paper, the first results of a broad study of static and moving flat plate wings for micro air vehicles (MAVs) are presented. Wind tunnel experiments with force measurements and particle image velocimetry (PIV) were performed in a specially designed wind tunnel environment for low Reynolds number investigations. Corresponding numerical flow simulations were also carried out. Effects of the wing shape (elliptical and rectangular), the Reynolds number (18, 000, 36, 000 and 108, 000) and the kinematics using different motion forms of pure plunge and combined pitch/plunge with a reduced frequency of k = 0.2 are discussed.